Development of electrospun poly (vinyl alcohol)‐based bionanocomposite scaffolds for bone tissue engineering. Issue 4 (14th January 2018) - Enayati, Mohammad Saied; Behzad, Tayebeh; Sajkiewicz, Pawel; Rafienia, Mohammad; Bagheri, Rouhollah; Ghasemi‐Mobarakeh, Laleh; Kolbuk, Dorota; Pahlevanneshan, Zari; Bonakdar, Shahin H.
Abstract: The article is focused on the role of nanohydroxy apatite (nHAp) and cellulose nanofibers (CNFs) as fillers in the electrospun poly (vinyl alcohol) (ES‐PVA) nanofibers for bone tissue engineering (TE). Fibrous scaffolds of PVA, PVA/nHAp (10 wt.%), and PVA/nHAp(10 wt.%)/CNF(3 wt.%) were successfully fabricated and characterized. Tensile test on electrospun PVA/nHAp10 and PVA/nHAp10/CNF3 revealed a three‐fold and seven‐fold increase in modulus compared with pure ES‐PVA (45.45 ± 4.77). Although, nanofiller loading slightly reduced the porosity percentage, all scaffolds had porosity higher than 70%. In addition, contact angle test proved the great hydrophilicity of scaffolds. The presence of fillers reduced in vitro biodegradation rate in PBS while accelerates biomineralization in simulated body fluid (SBF). Furthermore, cell viability, cell attachment, and functional activity of osteoblast MG‐63 cells were studied on scaffolds showing higher cellular activity for scaffolds with nanofillers. Generally, the obtained results confirm that the 3‐componemnt fibrous scaffold of PVA/nHAp/CNF has promising potential in hard TE. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 1111–1120, 2018.